The ‘Cornelia frente al espejo’ machine: sub-versions of gender and identity (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2022)
The following article analyzes the story “Cornelia frente al espejo,” written by Silvina Ocampo in 1988, and the movie released in 2012 with homonymous title, directed by Daniel Rosenfeld, as one composition. To that end, elements and concepts of the Feminist Film Theory, Queer Theories and French Post-Structuralism are taken into consideration. Far from pretending to position itself as a literary and/or film review ofeach one of the works individually, this article aims at distinguishing the operations performed by the text-movie machine at play with questions on gender (or, more precisely, the process of genderization) and identity. In this sense, both pieces -with their mutual interplays- are presented in one composition as a semiotic-narrative corpus that works as foundations on and from which the building of a reader-spectator with specific features may be distinguished. The various affective tonalities, images, symbols and disruptions offered by the text-movie machine may also be identified.
Keywords: technologies; gender; identity; feminity